Problematika Gratifikasi Seksual Sebagai Tindak Pidana Korupsi dalam Perspektif Hukum Positif Indonesia - Putra Sayfan, Heggel; Liyus, Herry; Arfa, Nys (Faculty of Law, Universitas Jambi, 2026)
The phenomenon of sexual gratification has not been explicitly regulated within the Indonesian legal system, despite its practical occurrence and its potential to undermine the integrity and independence of public officials. This regulatory gap creates uncertainty in legal qualification and poses evidentiary challenges, particularly when gratification is provided in the form of non-material sexual services. This study aims to analyze the legal status of sexual gratification within Indonesian positive law and to formulate an argumentative legal construction to qualify it as a corruption offense under Law Number 20 of 2001 concerning the Eradication of Corruption. The research employs a normative legal method using statutory and conceptual approaches, supported by an extensive interpretative analysis of the elements of gratification. The findings indicate that the phrase “other facilities” in Article 12B of the Anti-Corruption Law can be interpreted systematically and teleologically to encompass sexual gratification as a form of non-material benefit that may influence the independence of public officials. However, the absence of an explicit definition results in normative ambiguity and evidentiary difficulties, particularly in proving the causal relationship between the provision of sexual services and the abuse of authority. The scientific contribution of this study lies in formulating a juridical construction of sexual gratification as part of non-material gratification within the corruption framework, while also proposing qualification parameters consisting of the element of provision, positional relationship, and the intent to influence decision-making. This study concludes that sexual gratification may be qualified as a corruption offense through an extensive interpretation of Article 12B of the Anti-Corruption Law and recommends normative clarification to ensure legal certainty and enhance the effectiveness of law enforcement against non-material forms of corruption. ABSTRAK Fenomena gratifikasi seksual belum diatur secara eksplisit dalam sistem hukum Indonesia, padahal praktiknya berpotensi merusak integritas dan independensi penyelenggara negara. Kekosongan pengaturan ini menimbulkan ketidakpastian dalam kualifikasi yuridis serta hambatan pembuktian ketika gratifikasi diberikan dalam bentuk layanan seksual yang bersifat non-materiil. Penelitian ini bertujuan menganalisis status gratifikasi seksual dalam hukum positif Indonesia dan merumuskan konstruksi argumentatif untuk mengualifikasikannya sebagai tindak pidana korupsi dalam kerangka Undang-Undang Nomor 20 Tahun 2001 tentang Pemberantasan Tindak Pidana Korupsi. Penelitian menggunakan metode hukum normatif dengan pendekatan perundang-undangan dan konseptual, disertai analisis penafsiran ekstensif terhadap unsur gratifikasi. Hasil penelitian menunjukkan bahwa frasa “fasilitas lainnya” dalam Pasal 12B UU Tipikor secara sistematis dan teleologis dapat ditafsirkan mencakup gratifikasi seksual sebagai keuntungan non-materiil yang memengaruhi independensi pejabat publik. Namun demikian, tidak adanya definisi eksplisit menyebabkan ambiguitas norma serta problematika pembuktian, terutama terkait pembuktian hubungan kausal antara pemberian layanan seksual dan penyalahgunaan kewenangan. Kontribusi ilmiah penelitian ini terletak pada perumusan konstruksi yuridis gratifikasi seksual sebagai bagian dari gratifikasi non-materiil dalam rezim korupsi, sekaligus menawarkan parameter kualifikasi yang meliputi unsur pemberian, relasi jabatan, dan tujuan memengaruhi keputusan. Penelitian ini menyimpulkan bahwa gratifikasi seksual dapat dikualifikasikan sebagai tindak pidana korupsi melalui penafsiran ekstensif Pasal 12B UU Tipikor, serta merekomendasikan penegasan normatif guna menjamin kepastian hukum dan efektivitas penegakan hukum terhadap bentuk korupsi non-materiil.